High rate of invasive fungal infections during early cycles of azacitidine for patients with acute myeloid leukemia - Wang, Sing-Ting; Chou, Chia-Huei; Chen, Tzu-Ting; Lin, Ching-Chan; Bai, Li-Yuan; Yeh, Shih-Peng; Ho, Mao-Wang; Lien, Ming-Yu (Frontiers in Cellular and Infection Microbiology, 2022)
Background Acute myeloid leukemia (AML) is a form of cancer that is characterized by infiltration of the bone marrow, blood, and other tissues by proliferative, clonal, abnormally differentiated, and occasionally poorly differentiated cells of the hematopoietic system. Patients with acute myeloid leukemia (AML) receiving azacitidine (AZA) alone or in combination with venetoclax (VEN-AZA) are at increased risk for invasive fungal infections (IFIs). We compared the incidence and risk of IFI during these treatment regimens in a single Taiwan hospital. Materials and methods A total of 61 patients with AML received at least one course of AZA in the hematology ward of China Medical University Hospital (Taichung, Taiwan) between September 2012 and June 2020. Thirty-eight patients (62.3%) received AZA monotherapy; 23 (37.7%) received VEN-AZA. Results Incidence rates of probable and proven IFI were 18% and 1.6%, respectively, during AZA treatment. One proven case of Fusarium spp. infection was isolated by skin and soft tissue culture. Most (75%) IFI cases occurred during the first cycle of AZA therapy. Half of all IFI cases occurred in patients with prolonged neutropenia. The risk of IFI was significantly higher for the European LeukemiaNet (ELN) nonfavorable-risk group (intermediate- and adverse-risk group) versus the ELN favorable-risk group and for patients with prolonged neutropenia versus those without (P<0.05 for both comparisons). In this study, median OS did not differ significantly between patients with and without IFIs during AZA-containing regimens (14.6 months vs 13.7 months; P=0.59). Conclusion The incidence of IFI was high in this AML cohort treated with AZA-containing regiments in Taiwan. The majority of IFI cases occurred during the early cycles of AZA (cycles 1–2). Prospective studies are needed to determine the optimal choice of antifungal prophylaxis agent during VEN-AZA therapy for AML.